التسيير الاحترازي للمخاطر الائتمانية وفقا للجنة بازل الدولية - فخاري, فاروق; سعيدي, يحي (جامعة الوادي - University of Eloued, 2016)
كنتيجة لتزايد حدة الأزمات المالية في كثير من دول العالم، وما انجر عنها من آثار سلبية على اقتصادياتها وصلت لدرجة انهيار كبريات بنوكها، وذلك بسبب القصور الذي عرفته في تسير المخاطر الإئتمانية والمخاطر الأخرى، جاءت مقررات بازل الثلاثة بقواعد احترازية تنظم عمل البنوك بشكل موحد عالميا في ميدان تسيير المخاطر البنكية، لهذا يتناول هذا المقال تحليل المضمون النظري للتطورات التي عرفتها القواعد الإحترازية للجنة بازل الدولية في مجال تدنية المخاطر الإئتمانية في البنوك وكيفية تسييرها. As a result of the increased intensity of financial crises in many countries of the world, and the negative effects on their economies which reached the extent to the collapse of its leading banks, Because of the shortcomings identified in moving the credit risks and other hazards, came the decisions of the Basel Convention three precautionary rules governing the work of banks uniformly globally in the field of running banking risks. This article deals with the analysis of theoretical content of the developments witnessed by the precautionary rules of the Basel Committee in the field of minimizing the credit risks in banks and their management.
مقال
Keywords: تسيير المخاطر الإئتمانية، لجنة بازل، قواعد بازل الإحترازية.: Credit Risks Management - Basel Committee - Basel Rules Precautionary Measures.